Joint coding and decision feedback equalization for broadband wireless channels. - Ariyavisitakul, S.L.
This paper introduces a new approach for joint convolutional coding and decision feedback equalization (DPE). To minimize error propagation, the DFE uses a combination of soft decisions and delayed tentative decisions to cancel intersymbol interference (ISI). Soft decisions are obtained by passing the DFE output through a (soft) nonlinear device. This simple method is shown to perform almost as well as an optimum soft feedback approach on wireless channels with diversity. Tentative decisions from the Viterbi decoder are used to cancel ISI due to multipath with large delays, thus remedying the increasing effect of error propagation in channels with large delay spreads. We consider the use of this soft/delayed feedback DFE (S/D-DFE) technique in broadband wireless channels (with delay spreads up to several tens of the symbol period) typical in high-bitrate mobile data applications. Simulation results indicate that the proposed joint coding and S/D-DFE technique performs to within 1-2 dB [in required signal-to-noise ratio (SNR)] of an ideal coded DFE without error propagation. When combined with antenna diversity and a reduced-complexity DFE concept with adaptive feedforward tap assignment, it provides high packet throughput against Rayleigh fading, severe delay spreads, and high Doppler rates
Keywords: DFE; ISI cancellation; Rayleigh fading; SNR; Viterbi decoder; Adaptive feedforward tap assignment; Antenna diversity; Broadband wireless channels; Convolutional coding; Decision feedback equalization; Delayed tentative decisions; Error propagation; High Doppler rates; High packet throughput; High-bitrate mobile data applications; Intersymbol interference; Large delay spreads; Multipath; Nonlinear device; Optimum soft feedback; Reduced-complexity DFE; Signal-to-noise ratio; Soft decisions; Wireless channels